2021
DOI: 10.37897/rjn.2021.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of cerebral toxoplasmosis in HIV patients: A systematic review

Abstract: Introduction. Cerebral toxoplasmosis is one of the diseases of the central nervous system that can occur in people with AIDS. Cerebral toxoplasmosis occupies third place among fatal diseases that can occur in people with AIDS. Prevalence of toxoplasmosis is about 25-30% of the world’s human population, and in Asia it is as high as 40%. Risk factors for developing cerebral toxoplasmosis is needed to be sought to to find out risk factors that triggers and acts as protective factors for toxoplasmosis cerebral in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Nesse sentido, Azovtseva et al 1 verificaram que indivíduos com menor tempo de uso da TARV possuem maiores probabilidades de apresentar dano cerebral grave quando comparados àqueles com um tratamento mais longo. Assim, o uso regular da TARV e o tratamento profilático da NTX podem desempenhar papel protetor nesses indivíduos e reduzir o risco de dano cerebral grave 1,26 . Além disso, ressalta-se o acompanhamento da sorologia para a toxoplasmose como um fator preventivo, visto que, na maioria dos casos, ela pode se apresentar assintomática 27 , gerando um subdiagnóstico.…”
Section: Discussionunclassified
“…Nesse sentido, Azovtseva et al 1 verificaram que indivíduos com menor tempo de uso da TARV possuem maiores probabilidades de apresentar dano cerebral grave quando comparados àqueles com um tratamento mais longo. Assim, o uso regular da TARV e o tratamento profilático da NTX podem desempenhar papel protetor nesses indivíduos e reduzir o risco de dano cerebral grave 1,26 . Além disso, ressalta-se o acompanhamento da sorologia para a toxoplasmose como um fator preventivo, visto que, na maioria dos casos, ela pode se apresentar assintomática 27 , gerando um subdiagnóstico.…”
Section: Discussionunclassified
“…20 As such, the results of a recent meta-analysis revealed that the risk of cerebral toxoplasmosis increases 27.94 times in PLWH with CD4 + T cells <100/mm 3 . 21 Hepatitis B virus (HBV) and hepatitis C virus (HCV) are a major public health concern, especially among HIV infected patients. 22,23 As HIV, HBV, and HCV share similar transmission routes (e.g., sexual route, drug injection, and needle stick injury), co-infection with these viruses is more common than in the general population.…”
Section: Introductionmentioning
confidence: 99%
“… 20 As such, the results of a recent meta‐analysis revealed that the risk of cerebral toxoplasmosis increases 27.94 times in PLWH with CD4 + T cells <100/mm 3 . 21 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation